2019
DOI: 10.18632/aging.102236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age-dependent changes in cell size on endothelial cell proliferation and senescence through YAP1

Abstract: Angiogenesis – the growth of new blood capillaries- is impaired in aging animals. Biophysical factors such as changes in cell size control endothelial cell (EC) proliferation and differentiation. However, the effects of aging on EC size and the mechanism by which changes in cell size control age-dependent decline in EC proliferation are largely unknown. Here, we have demonstrated that aged ECs are larger than young ECs and that age-dependent increases in EC size control EC proliferation and senescence through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…To further study age-dependent changes in vascular formation in vivo , we used the fibrin gel implantation system, in which young vs. aged human adipose ECs were mixed in the gel [ 47 ], and characterized vascular formation in the gel. Consistent with previous report [ 47 ], vessel formation derived from supplemented ECs in the gel was attenuated when gel mixed with GFP-labeled aged ECs was implanted under the skin of adult immunocompromised NSG mice. Vascular area was 23% lower than that in the gel supplemented with young ECs ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further study age-dependent changes in vascular formation in vivo , we used the fibrin gel implantation system, in which young vs. aged human adipose ECs were mixed in the gel [ 47 ], and characterized vascular formation in the gel. Consistent with previous report [ 47 ], vessel formation derived from supplemented ECs in the gel was attenuated when gel mixed with GFP-labeled aged ECs was implanted under the skin of adult immunocompromised NSG mice. Vascular area was 23% lower than that in the gel supplemented with young ECs ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that age-related lung diseases, such as pulmonary fibrosis and accompanied pulmonary hypertension, in which changes in mechanical environment are involved in the disease progression [ 85 87 ], are prevented in Twist1 fl/fl /Tie2 - cre mice [ 18 , 27 ]. Other transcription factors and co-factors (e.g., TFII-I, GATA2, YAP1) that sense mechanical forces interact with Twist1, control angiogenesis [ 47 , 50 , 71 , 75 , 88 ], and contribute to age-related lung diseases ( e.g., pulmonary fibrosis, pulmonary hypertension) [ 85 87 ]. Thus, Twist1 senses age-dependent changes in the mechanical forces to control angiogenesis and lung regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EC density also changes dynamically during vascular remodelling [7]. Though changes in density have been shown to be independent of replication [7], ECs undergo drastic changes in surface area without replicating [13,14]. A complete understanding of vascular remodelling can only be achieved by taking into account all of these interlinked factors.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular senescence presents multiple cellular and molecular features [1], which may function as suitable biomarkers or therapeutic targets. Senescent cells generally demonstrate an enlarged and flattened cell morphology [27] and expanded nucleoli [28,29], enhanced senescence-associated beta-galactosidase (SA-β-gal) activity [30], telomere shortening, elevation of the cyclin-dependent kinase inhibitor p16 [11,31] or p21 [32], macromolecular damage and metabolism dysfunction [1]. The prominent characteristic of senescent cells is the senescence-associated secretory phenotype (SASP).…”
Section: Features Of Cellular Senescencementioning
confidence: 99%